Origins of the Tājika System of Astrological Aspects and Dignities - Gansten, Martin (History of Science in South Asia, 2018)
The astrological doctrines of aspects and planetary dignities found in the authoritative texts of the Tājika (Sanskritized Perso-Arabic) school are examined with respect to their origins and historical development, with particular emphasis on Balabhadra’s encyclopaedic Hāyanaratna (1649) and its quotations from the perhaps earliest work of the school, Samarasiṃha’s Tājikaśāstra (thirteenth century). It is argued that a major source of these doctrines is Sahl ibn Bishr’s Arabic-language introduction to astrology (ninth century), possibly in abbreviated or paraphrased form. Several of the constituent ideas have been imperfectly understood by their Indian epitomists, resulting in reinterpretations and innovations.